Inclusion as Social Justice. A research project in Italian middle schools - Giovanna Malusà (University of Bologna, 2020)
In an atmosphere of growing racism, xenophobia, intolerance and fear of diversity, schools, too, are faced with serious challenges. Taking-from a non-neutral perspective-the educational achievement of students of migrant origin as a parameter by which to evaluate the effectiveness of learning paths, we find that huge problems remain in our school system, which require the education system to be given the explicit function of a social equalizer. Through a Grounded Theory critique-part of a complex mixed-method study-the processes of (non-)success of students from migrant backgrounds are analysed, with the aim of developing a theoretical model for planning learning paths that work for all students. The research involved-through ethnographic observation, interviews and questionnaires-principals, teachers and students from five middle schools in the provinces of Trento and Turin. The multidimensional model which emerges demonstrates the importance of collective action which involves multiple links between schools, the political arena and the territory, following in the footsteps of both Lorenzo Milani and Paulo Freire.